Dimensionality and Measurement Invariance of the Italian Version of the EORTC QLQ-C30 in Postoperative Lung Cancer Patients - Marzorati, Chiara; Monzani, Dario; Mazzocco, Ketti; Pavan, Francesca; Monturano, Massimo; Pravettoni, Gabriella (Frontiers in Psychology, 2019)
Background This study aims to validate and evaluate the psychometric properties and measurement invariance of the Italian version of the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-Core 30 (QLQ-C30), which is a measure of Quality of Life (QoL) for lung cancer patients after surgery. Methods 167 lung cancer patients completed the Italian version of the EORTC QLQ-C30 questionnaire at 30 days after they received a lobectomy. The factor structure of this scale was assessed by performing Confirmatory Factor Analysis (CFA). Measurement invariance was evaluated by considering differential item functioning (DIF) due to age, gender, and type of surgery (i.e., robot- or not robot-assisted). Results The CFA demonstrated the validity of the factor structure of the EORTC QLQ-C30 in assessing overall health and eight distinct subscales of adverse events and functioning. Moreover, the results highlighted a minimal DIF with only trivial consequences on measurement invariance. Specifically, the DIF did not affect the mean differences of latent scores of QoL between patients undergoing robot-assisted surgery or traditional surgery. Conclusions These findings supported the validity and suitability of the EORTC QLQ-C30 for the assessment of Quality of Life in lung cancer patients of diverse ages and genders undergoing lobectomy with or without robot-assisted surgery.